The Narrator's Perception of Homosexual in Catetan Poean Rere By Ai Koraliati And My Cousin Is Gay By Lia Indra Andriana - Zulfikar Alamsyah; Lina Meilinawati Rahayu; Teddi Muhtadin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to reveal the narrator's perception of homosexuality and the ideology contained in the Noveletet Catetan Poéan Réré and the teenlit Novelet My Cousin is Gay. The method used in this research is descriptive analytic. Reading and taking notes are the data collection techniques of this study. The data processing technique used is data triangulation. The results of this study indicate that there are eight perceptions of the narrator towards homosexuals, namely homosexuality as a disgrace that must be hidden, a wrong deed, a disease that must be cured, a person who is strange or not in general, a difficult life to live, a bad person, a trial that given by God, and one's life choices that must be respected. There are two ideologies in Catetan Poéan Réré's Noveletet, namely the ideology of conservatism and the ideology of theism. Likewise in the teenlit Novelet My Cousin is Gay which has two ideologies, namely the ideology of conservatism and the ideology of liberalism. The conclusion in this study is that negative perceptions of homosexual behavior are more dominant in both literary works. The ideologies in the Noveletet Catetan Poéan Réré have a close correlation because the two ideologies try to maintain heterosexuality in their society. The author and the narrator have the same voice in addressing homosexual behavior. While the ideology in the teenlit Novelet My Cousin is Gay has no correlation. The author and several characters in the story have a conservatism ideology that tries to maintain heteronormativity. This is contrary to the ideology of liberalism that appears in the middle of the story through the narrator's point of view. Therefore, the writer and narrator in this Novelet do not have the same voice in dealing with homosexuals.